The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.brs.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

A case series exploring the effect of twenty sessions of repetitive transcranial magnetic stimulation (rTMS) on cannabis use and craving

Abstract: Fig. 1. a) Marijuana Craving Questionnaire Short Form (MCQ-SF) Total Score, recorded prior to each of the denoted treatment visits; and 1b) Average number of cannabis use sessions per day as measured by the Time Line Follow-back (TLFB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…A case series ( N = 3) suggested that rTMS directed to bilateral DLPFC for 20 sessions may reduced cannabis use and craving, with a large effect size (Cohen’s d = 1.2) 42 . Since these effects of rTMS may be mediated by targeting specific brain circuits 35 , it was critical to evaluate cannabis craving/withdrawal symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case series ( N = 3) suggested that rTMS directed to bilateral DLPFC for 20 sessions may reduced cannabis use and craving, with a large effect size (Cohen’s d = 1.2) 42 . Since these effects of rTMS may be mediated by targeting specific brain circuits 35 , it was critical to evaluate cannabis craving/withdrawal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…No significant changes in craving were found between active and sham groups. Recently, this group completed an open-label safety trial applying 20-sessions (10-Hz) to DLPFC over 2 weeks to nine individuals with CUD; only three completed the trial 42 . Thus, further research is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…The following sections briefly introduce behavioral and pharmacologic strategies that may facilitate neurobiobehavioral recovery and improve long-term outcomes. 2 Other approaches, including neuromodulation, are gaining momentum as possible interventions for substance use disorders 58 but will not be discussed.…”
Section: Intervention Strategiesmentioning
confidence: 99%
“…So, there is an urgent need to identify and develop novel therapeutic interventions for CUD. Recent advancements in human neuroscience have provided new adjuvant treatment options including noninvasive brain stimulation (NIBS) interventions for those individuals with CUD who desire to quit substance abuse based on targeting the neurocognitive processes (Kearney-Ramos & Haney, 2021;Sahlem et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In substance use disorders (SUDs), it has been reported that activity in the prefrontal cortex and its connectivity to the subcortical regions (including striatum and amygdala) that are related to addictive behaviors such as drug craving can be modulated by NIBS methods (Jansen et al, 2013;Ma, Sun, & Ku, 2019). Research on repetitive transcranial magnetic stimulation (rTMS) for the treatment of CUD showed encouraging results for enhancing drug craving or consumption (Kearney-Ramos & Haney, 2021;Martin-Rodriguez et al, 2021;Prashad, Dedrick, To, Vanneste, & Filbey, 2019;Sahlem, Baker, George, Malcolm, & McRae-Clark, 2018;Sahlem et al, 2020).…”
Section: Introductionmentioning
confidence: 99%